2005
DOI: 10.1021/bi047500f
|View full text |Cite
|
Sign up to set email alerts
|

Role of Putative Anion-Binding Sites in Cytoplasmic and Extracellular Channels ofNatronomonas pharaonisHalorhodopsin

Abstract: Natronomonas (Natronobacterium) pharaonis halorhodopsin (NpHR) is an inward light-driven Cl(-) ion pump. For efficient Cl(-) transport, the existence of Cl(-)-binding or -interacting sites in both extracellular (EC) and cytoplasmic (CP) channels is postulated. Candidates include Arg123 and Thr126 in EC channels and Lys215 and Thr218 in CP channels. The roles played by these amino acid residues in anion binding and in the photocycle have been investigated by mutation of the amino acid residues at these position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(128 citation statements)
references
References 55 publications
11
117
0
Order By: Relevance
“…Overall architectures viewed parallel to the membrane. Asn-98 in NM-R3) for Cl Ϫ transport (32)(33)(34). In addition, it was proposed that Asp-116 in KR2 (corresponding to Thr-102 in NM-R3) plays an important role in Na ϩ pumping, as estimated from the structure and mutant experiments (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Overall architectures viewed parallel to the membrane. Asn-98 in NM-R3) for Cl Ϫ transport (32)(33)(34). In addition, it was proposed that Asp-116 in KR2 (corresponding to Thr-102 in NM-R3) plays an important role in Na ϩ pumping, as estimated from the structure and mutant experiments (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…As KR2 is a light-driven sodium ion pump, NaR probably possesses a sodium-ion binding site. Chloride binds to HR as the RSB counterion, so that the binding can be monitored by colour change (l max change by 420 nm) 30 . In contrast, NaR shows little colour change between the presence and absence of sodium ions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 d), due to its less important role in chloride binding. In addition, atomic structures showed that the hydroxyl group (-OH) in Thr126 is not oriented directly toward chloride, and the anion binding preference for these residues was found to occur in the order of Arg123 > Ser130 > Thr126 (36), which explains the detected photocurrent signal in T126A. Therefore, this unique photocurrent signal is tightly associated with chloride.…”
Section: Critical Residues In Nphr Mediate This Unique Light-driven Pmentioning
confidence: 99%